Pengaruh Online Customer Review dan Diskon Harga terhadap Online Impulsive Buying Pengguna Shopee: Studi Kasus pada Mahasiswa Fakultas Ekonomi Angkatan 2022 - Ria Sombe; Althon K. Pongtuluran; Chrimesi Pagiu (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
This study aims to determine the effect of online customer reviews and price discounts partially and simultaneously on online impulsive buying of shopee users of the Faculty of Economics class of 2022. This study used quantitative research methods. The data collection procedure in this study is by making observations, distributing questionnaires / questionnaires and documentation. The results of the research obtained are that the online customer review variable partially negatively affects online impulsive buying of shopee users, students of the Faculty of Economics, class of 2022. The price discount variable partially has a positive and significant effect on online impulsive buying of students of the Faculty of Economics class of 2022 who are shope users. Simultaneously, the variables of online customer reviews and price discounts have a positive and significant effect on online impulsive buying.